Hungarian Monitoring, 20 June 1989 . [Magyar rádiófigyelő], 1989. június 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - TASS commentary on June 16 - More protests held in Romania over speeches held at Imre Nagy's funeral - Situation in Poland Domestic Affairs: - Károly Grósz's statement to Radio employees - Imre Pozsgay at National Peace Council on relations with neighboring countries Economy: - Interview with György Surányi, secretary of state at Planning Office, on the budget situation Külpolitika: - TASZSZ kommentár június 16-ról - Romániában újabb tiltakozó gyűléseket tartottak a Nagy Imre temetésén elhangzott beszédek miatt - Lengyel helyzetkép Belpolitika: - Grósz Károly nyilatkozata a rádió munkatársának - Pozsgay Imre az Országos Béketanács ülésén a szomszéd államokkal való viszonyról Gazdaság: - Interjú Surányi Györggyel, a Tervhivatal államtitkárával a költségvetés helyzetéről